Understanding dynamic linkages and technology spillover from Korea's Masan Free Export Zone - O'Flaherty, David Desmond (University of Ottawa (Canada), 2008)
Drawing upon the wealth of literature previously written about the Masan Free Export Zone (MAFEZ), this thesis will disentangle the conflicting information and hypotheses about the some of the zone's 'welfare benefits.' That is, the thesis will examine production linkages and technology spillover from the export processing zone (EPZ) itself to the greater economy. The vast literature already written on this subject is divergent, to say the least, and much of it is inconsistent with simple facts available in archival materials and exhaustively compiled statistical evidence. Therefore, this thesis will examine the extant literature on the zone and compare this with archival material gathered in South Korea to reinterpret the facts through a more holistic and interdisciplinary lens. This thesis will demonstrate that the establishment of MAFEZ was successful in creating such welfare benefits to the domestic Korean economy outside of the zone, and that such success was mostly policy-induced. Chapter One will introduce some of the divergent ideas and academic controversies about EPZs in general and MAFEZ in particular. Chapter Two will give a brief history of Korea's export-oriented industrialization drive, and how Korean Industrial Estates (IEs) and EPZs figured in this drive. It will also delineate important political and economic differences between Korean IEs and EPZs. Chapter Three will examine in detail production linkages from MAFEZ. Chapter Four will study technology spillover from the zone and the impact of such spillover. This thesis will conclude with an overview of the argument and an explication of some of the problems that MAFEZ, as a development tool, faced during its evolution and expansion.
Keywords: Economics, General.; Political Science, International Law and Relations.